Acts of conscience : World War II, mental institutions, and religious objectors - Taylor, Steven J., 1949- (Critical perspectives on disability., 2009)
"In the mid- to late 1940s, a group of young men rattled the psychiatric establishment by beaming a public spotlight on the squalid conditions and brutality in our nation⁰́₉s mental hospitals and training schools for people with psychiatric and intellectual disabilities."